Influence of Acetic Acid Pretreatment and its Residue on Bioethanol and Biogas Production from Water Hyacinth - Jose, Diana; Tawai, Atthasit; Divakaran, Divya; Sriariyanun, Malinee; Phakeenuya, Vanarat; Cheng, Yu-Shen; Tantayotai, Prapakorn (Applied Science and Engineering Progress, 2024)
Water hyacinth, an invasive species in natural water habitats, poses ecological challenges but also holds promise as a biofuel resource due to its abundant biomass. To optimize sugar yield for biofuel production, this study focuses on pretreating water hyacinth with acetic acid (AC) using Response Surface Methodology (RSM). Comparing AC, hydrochloric acid (HA), and untreated samples, AC-pretreated samples yielded the highest sugar content at 28.26 g/100 g of biomass, nearly 1.97 times higher than that of untreated samples. Additionally, AC-pretreated samples produced the maximum biogas (2573 mL) after 45 days of anaerobic digestion, while HA pretreatment yielded the highest ethanol production (9.32 g/L) within 48 h. The structural changes in the pretreated and untreated water hyacinth samples were compared using FTIR analysis, and the results showed that the pretreatment approaches exposed more cellulose to hydrolysis. Furthermore, the study investigated the impact of post-washing following acid pretreatment of water hyacinth and discovered that AC residues had no adverse effects, suggesting that the post-washing phase was unnecessary for ethanol production. These findings demonstrate that AC pretreatment can effectively enhance hydrolysis and biofuel production and that eliminating post-washing may reduce wastewater generated during the pretreatment process.